Download presentation
Presentation is loading. Please wait.
1
Matrix Multiplication
Example 1 By: Jeffrey Bivin Lake Zurich High School
2
Matrix Multiplication
3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X Row by Column
3
Matrix Multiplication
3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X Rows of the first matrix by Columns of the second matrix
4
Matrix Multiplication
3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X Rows of the first matrix by Columns of the second matrix
5
Matrix Multiplication
3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X Rows of the first matrix by Columns of the second matrix Jeff Bivin -- LZHS
6
Matrix Multiplication
3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X Rows of the first matrix by Columns of the second matrix
7
Matrix Multiplication
3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X Rows of the first matrix by Columns of the second matrix
8
Matrix Multiplication
3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X Rows of the first matrix by Columns of the second matrix
9
Matrix Multiplication
3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X Rows of the first matrix by Columns of the second matrix
10
Matrix Multiplication
3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X Rows of the first matrix by Columns of the second matrix
11
Matrix Multiplication
3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X Rows of the first matrix by Columns of the second matrix
12
Let’s Begin……….
13
Row 1 x Column 1 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 3 x x x 2 = 25
14
Row 1 x Column 1 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 3 x x x 2 = 25
15
Row 1 x Column 1 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 3 x x x 2 = 25
16
Row 1 x Column 1 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 = A(1,1)
17
3 x (-1) + 2 x 3 + 5 x 7 = 38 X Row 1 x Column 2 3 2 5 -2 1 4 6 9 5 -1
1 4 6 9 5 -1 2 3 7 4 X 3 x (-1) + 2 x x 7 = 38
18
3 x (-1) + 2 x 3 + 5 x 7 = 38 X Row 1 x Column 2 3 2 5 -2 1 4 6 9 5 -1
1 4 6 9 5 -1 2 3 7 4 X 3 x (-1) + 2 x x 7 = 38
19
3 x (-1) + 2 x 3 + 5 x 7 = 38 X Row 1 x Column 2 3 2 5 -2 1 4 6 9 5 -1
1 4 6 9 5 -1 2 3 7 4 X 3 x (-1) + 2 x x 7 = 38
20
Row 1 x Column 2 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 38 = A(1,2)
21
Row 1 x Column 3 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 3 x x x 4 = 40
22
Row 1 x Column 3 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 3 x x x 4 = 40
23
Row 1 x Column 3 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 3 x x x 4 = 40
24
Row 1 x Column 3 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 38 40 = A(1,3)
25
-2 x 5 + 0 x 0 + 1 x 2 = -8 X Row 2 x Column 1 3 2 5 -2 1 4 6 9 5 -1 2
1 4 6 9 5 -1 2 3 7 4 X -2 x x x 2 = -8
26
-2 x 5 + 0 x 0 + 1 x 2 = -8 X Row 2 x Column 1 3 2 5 -2 1 4 6 9 5 -1 2
1 4 6 9 5 -1 2 3 7 4 X -2 x x x 2 = -8
27
-2 x 5 + 0 x 0 + 1 x 2 = -8 X Row 2 x Column 1 3 2 5 -2 1 4 6 9 5 -1 2
1 4 6 9 5 -1 2 3 7 4 X -2 x x x 2 = -8
28
Row 2 x Column 1 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 38 40 -8 = A(2,1)
29
Row 2 x Column 2 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X
30
-2 x (-1) + 0 x 3 + 1 x 7 = 9 X Row 2 x Column 2 3 2 5 -2 1 4 6 9 5 -1
1 4 6 9 5 -1 2 3 7 4 X -2 x (-1) + 0 x x 7 = 9
31
-2 x (-1) + 0 x 3 + 1 x 7 = 9 X Row 2 x Column 2 3 2 5 -2 1 4 6 9 5 -1
1 4 6 9 5 -1 2 3 7 4 X -2 x (-1) + 0 x x 7 = 9
32
-2 x (-1) + 0 x 3 + 1 x 7 = 9 X Row 2 x Column 2 3 2 5 -2 1 4 6 9 5 -1
1 4 6 9 5 -1 2 3 7 4 X -2 x (-1) + 0 x x 7 = 9 Jeff Bivin -- LZHS
33
Row 2 x Column 2 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 38 40 -8 9 = A(2,2)
34
-2 x 2 + 0 x 7 + 1 x 4 = 0 X Row 2 x Column 3 3 2 5 -2 1 4 6 9 5 -1 2
1 4 6 9 5 -1 2 3 7 4 X -2 x x x 4 = 0 Jeff Bivin -- LZHS
35
-2 x 2 + 0 x 7 + 1 x 4 = 0 X Row 2 x Column 3 3 2 5 -2 1 4 6 9 5 -1 2
1 4 6 9 5 -1 2 3 7 4 X -2 x x x 4 = 0 Jeff Bivin -- LZHS
36
-2 x 2 + 0 x 7 + 1 x 4 = 0 X Row 2 x Column 3 3 2 5 -2 1 4 6 9 5 -1 2
1 4 6 9 5 -1 2 3 7 4 X -2 x x x 4 = 0
37
Row 2 x Column 3 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 38 40 -8 9 = A(2,3) Jeff Bivin -- LZHS
38
Row 3 x Column 1 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 4 x x x 2 = 38 Jeff Bivin -- LZHS
39
Row 3 x Column 1 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 4 x x x 2 = 38
40
Row 3 x Column 1 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 4 x x x 2 = 38
41
Row 3 x Column 1 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 38 40 -8 9 = A(3,1)
42
4 x (-1) + 6 x 3 + 9 x 7 = 77 X Row 3 x Column 2 3 2 5 -2 1 4 6 9 5 -1
1 4 6 9 5 -1 2 3 7 4 X 4 x (-1) + 6 x x 7 = 77 Jeff Bivin -- LZHS
43
4 x (-1) + 6 x 3 + 9 x 7 = 77 X Row 3 x Column 2 3 2 5 -2 1 4 6 9 5 -1
1 4 6 9 5 -1 2 3 7 4 X 4 x (-1) + 6 x x 7 = 77
44
4 x (-1) + 6 x 3 + 9 x 7 = 77 X Row 3 x Column 2 3 2 5 -2 1 4 6 9 5 -1
1 4 6 9 5 -1 2 3 7 4 X 4 x (-1) + 6 x x 7 = 77
45
Row 3 x Column 2 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 38 40 -8 9 77 = A(3,2)
46
Row 3 x Column 3 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 4 x x x 4 = 86
47
Row 3 x Column 3 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 4 x x x 4 = 86
48
Row 3 x Column 3 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 4 x x x 4 = 86 Jeff Bivin -- LZHS
49
Row 3 x Column 3 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 38 40 -8 9 77 86 A(3,3)
50
Matrix Multiplication
3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 38 40 -8 9 77 86 =
51
Matrix Multiplication
3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 38 40 -8 9 77 86 =
52
Matrix Multiplication
3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 38 40 -8 9 77 86 =
53
A Quick Review
54
Row 1 x Column 1 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 = A(1,1)
55
Row 1 x Column 2 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 38 = A(1,2)
56
Row 1 x Column 3 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 38 40 = A(1,3)
57
Row 2 x Column 1 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 38 40 -8 = A(2,1)
58
Row 2 x Column 2 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 38 40 -8 9 = A(2,2)
59
Row 2 x Column 3 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 38 40 -8 9 = A(2,3)
60
Row 3 x Column 1 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 38 40 -8 9 = A(3,1)
61
Row 3 x Column 2 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 38 40 -8 9 77 = A(3,2)
62
Row 3 x Column 3 3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 38 40 -8 9 77 86 = A(3,3)
63
Matrix Multiplication
3 2 5 -2 1 4 6 9 5 -1 2 3 7 4 X 25 38 40 -8 9 77 86 =
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.